Editor About Consensus on Obstetric Hemorrhage published by ACOG - Pacheco Romero, José (2015)
The American College of Obstetricians and Gynecologists has published a Consensus on Obstetric Hemorrhage, referred mainly to postpartum hemorrhage (1). It is considered in writing that obstetric hemorrhage is the most common and severe complication of childbirth which would have the best chance of preventing maternal mortality. He notes that recent research suggests that obstetric hemorrhage rates are increasing in developed countries, including the US, and rates of severe maternal morbidity associated with excess bleeding morbidities associated with obstetric and other medical conditions. Therefore, the group Partnership for Safe Motherhood, which belongs to the Council for Patient Safety in Health Care of Women and representing major professional organizations in the field, has prepared this Consensus on Management of Obstetric Hemorrhage, which can be summarized in four main points: 1) Be prepared 2) Recognition and Prevention of the problem in each patient 3) Immediate response at each bleeding; and 4) Communication and learning in each unit involved.